Teacher Performance Analysis in the Learning Process - Wahyu, Sri; Rizal, Fahmi; Syah, Nurhasan (Journal of Education Reseach and Evaluation, 2021)
Educational problems that occur today include the low quality of education at each level of the education unit. It is due to low teacher performance. This study aimed to analyze teacher performance in the learning planning process, learning implementation, and learning evaluation. This research method is carried out using a qualitative approach research method that produces descriptive data in written or spoken words from the teachers that can be observed. The interviewing instruments are interviews, observation, and documentation. Data analysis techniques are used through data reduction, data display, and verification (concluding). Based on this study's findings, it is concluded that the teacher's performance in lesson planning has met the criteria that must be done in learning, learning materials, learning resources, learning media, and assessment of learning outcomes. By making the lesson plan, the teacher has carried out the lesson planning well. The teacher's performance in implementing learning has been carried out well. It can be seen from the learning activities that have been created by the teacher in the classroom. Teacher performance in learning evaluation includes evaluating good learning outcomes by implementing structured remedial and enrichment.